2013
DOI: 10.1242/jcs.116129
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligases RNF126 and Rabring7 regulate endosomal sorting of the Epidermal Growth Factor Receptor

Abstract: SummaryActivation of the epidermal growth factor receptor (EGFR) results in internalization and ubiquitin-dependent endosomal sorting, leading to lysosomal degradation. Here we describe the role of the RING-finger-domain-containing protein RNF126 and the related protein, Rabring7 in EGFR endosomal sorting. We demonstrate that RNF126 specifies K48-linked chains with UbcH5b and also functions with Ubc13/Uev1a to form K63-linked chains in vitro. RNF126 and Rabring7 associate with the EGFR through a ubiquitin-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 41 publications
2
73
2
Order By: Relevance
“…Indeed, assays with a dominant-negative mutant of Rab7 impaired BCA2 function and led to increased Gag levels, and therefore, a substantial rescue in virus release. Moreover, BCA2 has recently been shown to route EGFR for endosomal sorting [42], [43], further corroborating the connection of BCA2 with the endo-lysosomal pathway.…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, assays with a dominant-negative mutant of Rab7 impaired BCA2 function and led to increased Gag levels, and therefore, a substantial rescue in virus release. Moreover, BCA2 has recently been shown to route EGFR for endosomal sorting [42], [43], further corroborating the connection of BCA2 with the endo-lysosomal pathway.…”
Section: Discussionmentioning
confidence: 60%
“…It is possible that RNF8 catalyzes an initial ubiquitylation of Ku80 and that the ubiquitin chain is then extended by RNF126. This scenario is supported by the recent observation that the zinc finger domain of RNF126 binds directly to ubiquitin (24).…”
Section: Discussionmentioning
confidence: 65%
“…Polyubiquitylation of the epidermal growth factor receptor (EGFR) on the endosomal membrane by RNF126 was thus shown to promote its lysosomal sorting and degradation (24). RNF126 also regulates trafficking of another membrane protein, the mannose-6-phosphate receptor, from endosomes to the Golgi complex in a manner dependent on its RING finger domain, although the substrate of RNF126 in this regulation was not identified (26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study suggested that RNF126 interacted with the EGFR through a ubiquitin‐binding zinc finger domain and promoted the ubiquitylation of EGFR 9. To determine the function of RNF126 in tongue cancer development, we focused on the downstream signaling pathway of EGFR.…”
Section: Resultsmentioning
confidence: 99%
“…First, the substrates of RNF126, like p21 14, Bag6 15, and EGFR 9 are involved in oncogenesis. It promotes cell proliferation partially through degrading p21 14.…”
Section: Discussionmentioning
confidence: 99%